2017
DOI: 10.1097/sih.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of Pictorial Guide for Improved Accuracy of Visual Blood Loss Estimation in Cesarean Delivery

Abstract: An institution-specific pictorial guide is effective at improving the accuracy of visual blood loss estimation in a simulation and may help improve clinical care in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The study results are heterogeneous, so there are different results about the influence of different factors of professional experience, gender, age on the accuracy of the estimate. Even the use of pictograms and other measures does not lead to clear improvements (for a detailed description of the various studies, please refer to Supplement 2) [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Visual Estimationmentioning
confidence: 99%
“…The study results are heterogeneous, so there are different results about the influence of different factors of professional experience, gender, age on the accuracy of the estimate. Even the use of pictograms and other measures does not lead to clear improvements (for a detailed description of the various studies, please refer to Supplement 2) [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Visual Estimationmentioning
confidence: 99%
“…Simulation has been used effectively to assess the accuracy of different methods of blood loss quantification. The use of a pictorial guide as a means to assess blood loss during a simulated cesarean delivery was evaluated by Homcha and colleagues 37 comparing assessments of blood loss prior to and after use of the guide. Prior to use of the pictorial guide, they observed a more than 25% overestimation of blood loss, whereas use of the guide revealed an increase from 7% to 24% of accurate estimation defined as an estimate within 5% of the actual volume lost.…”
Section: Simulation-based Assessment Of the Work Environment And Practice Methodsmentioning
confidence: 99%
“…A lack of regular feedback on the actual amount of blood loss may be an explanation for the missing learning effect. It has been demonstrated that the visual estimation method can be improved through practical training and tools like pictograms [3,[6][7][8][9][10][11]. In addition to blood collection canisters, surgical sponges play a major role in blood loss estimation, as they absorb blood directly from the surgical field.…”
Section: Plos Onementioning
confidence: 99%
“…Accounting for this issue, several studies were carried out to quantify its inaccuracy and to improve the visually based method of estimation. Focus laid on practical or web-based training in simulated scenarios [3,[6][7][8][9][10][11]. Several studies investigated visual estimation of blood loss and one study examined the influence of fluid colour on estimation accuracy [12].…”
Section: Introductionmentioning
confidence: 99%